(x-2)(x+2)-(2x-1)(2x+1)
x mũ 2 -2 mũ 2
=x^3-8-2(x^2-1)
=x^3-8-2x^2+2
=x^3-2x^2-6
(x-2)(x+2)-(2x-1)(2x+1)
x mũ 2 -2 mũ 2
=x^3-8-2(x^2-1)
=x^3-8-2x^2+2
=x^3-2x^2-6
1.giải phương trình :
1)1 + 2/x-1 + 1/x+3=x^2+2x-7/x^2+2x-3
2)x/x^2+5x+6=2/x^2+3x+2 (x=3)
3)1/x^2+9x+20 - 1/x^2+8x+12=x^2-2x-33/x^2+8x+15 (x=-5,7)
4)x+5/3x-6 - 1/2=2x-3/2x-4 (x=25/7)
5)x-1/x^3+1 + 2x+3/x^2-x+1=2x+4/x+1 - 2(x=0)
Giải phương trình:
a) x+1/x-2 + x-1/x+2 = 2(x^2+2)/x^2-4
b) 2x+1/x^2-5x+4 + 5/x-1 = 2/x-4
c) 2x^2/x^3-8 + x+1/x^2+7x+12 +1/x^2+9x+20 + 1/x^2+11x+30 = 1/15
d) x+4/2x^2-5x+2 + x+1/2x^2-7x+3 = 2x+5/2x^2-7x+3
2x ^3 -5x^2+4x-1) : (2x+1)
(x63 -2x+4) ; (x+2)
(6x^3 - 19x^2+23x-12):(2x-3)
(x^4 - 2 x ^3 - 1+ 2 x ):(x^2 - 1)
(6x^3 - 5x^2 + 4x -1 ) : (2x^2-x+1)
(x^4 -5x^2+4):(x^2-3x+2)
giải phương trình:
a, 1+2x-5/6=3-x/4
b, x+3/x+1+x-2/x=2
c, x-2/x+2+3/x-2=x^2-11/x^2-4
d,2/x+1-1/x-2=3x-11/x+1*x-2
e,x+2/x-2-1/x=2/x^2-2x
f, x+2/x-2-1/x=2/x*(x-2)
g,3x-1/x-1=2x+5/x-3
h,2x/2x-1+x/2x+1=1+4/2x-1*2x+1
mình cần bài này gấp ạ
Giải các phương trình sau bằng cách đưa về dạng ax + b = 0 :
1. a) 5 - (x - 6) = 4(3 - 2x)
b) 2x(x + 2)^2 - 8x^2 = 2(x - 2)( x^2 + 2x + 4)
c) 7 - (2x + 4) = - (x + 4)
d) (x - 2)^3 + (3x - 1)(3x + 1) = (x + 1)^3
e) (x + 1)(2x - 3) = (2x - 1)(x + 5)
f) (x - 1)^3 - x(x + 1)^2 = 5x(2 - x ) - 11(x +2)
g) (x-1) - (2x - 1 ) = 9 - x
h) (x-3)(x+4) - 2(3x - 2) = (x-4)^2
i) x(x+3)^2 - 3x = (x + 2)^3 + 1
j) (x + 1)(x^2 - x + 1) - 2x = x(x + 1)(x-1)
(2x-1/x)^4
(2x^2-1/x)^4
[(2x)^2-1/x]^4
[(2x)^2-1/x^2]^4
(2x-1/x)^4
(2x^2-1/x)^4
[(2x)^2-1/x]^4
[(2x)^2-1/x^2]^4
(2x-1/x)^4
(2x^2-1/x)^4
[(2x)^2-1/x]^4
[(2x)^2-1/x^2]^4
(2x-1/x)^4
(2x^2-1/x)^4
[(2x)^2-1/x]^4
[(2x)^2-1/x^2]^4
a)x-3/x-2 + x-2/x-4 = -1
b)3x + 12 = 0
c)5 + 2x = x - 5
d)2x(x - 2) + 5(x - 2) = 0
e)3x-4/2 = 4x+1/3
f)2x/x-1 - x/x+1 =1
g)2x/x-1 + 3-2x/x+2 = 6/(x-1)(x+2)